Optimization of chemical engineering problems with EMSO software - Henrique, João Paulo; Sousa, Ruy; Secchi, Argimiro R.; Ravagnani, Mauro A. S. S.; Costa, Caliane B. B. (Computer applications in engineering education, 2018)
EMSO software, a free tool for teaching and academic research, presents a favorable environment for simulation and optimization of chemical engineering problems. Although its use in research activities have been demonstrated in the literature, its application as a supporting tool for educational purposes in process systems engineering courses has not been evaluated. The objective of this paper is to demonstrate that this software is suitable as a tool for educational purposes in process systems engineering courses at undergraduate (complementary elective subject) and graduate levels. To accomplish this task, different cases studies, encompassing different sort of programming formulations, are proposed and solved with different solvers in EMSO.